The storm petrel and the owl of Athena - Halle, Louis Joseph, 1910-1998 (Princeton legacy library., 1970)
The first part of this book describes a wide variety of seabirds from the author's personal observation and knowledge of their ways; the second offers reflective essays on the general theme of birds in their relation to man. Originally published in 1970. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.